Livestock vaccines: Digital delivery service - Domfeh, Kofi Adu (Technical Centre for Agricultural and Rural Cooperation, 2019)
Women livestock farmers in rural Ghana are receiving veterinary services delivered to their door at the tap of a finger when they register with Cowtribe's app.